Compositions and methods for treating peripheral arterial disease - THOMPSON DAVID; NITSCHKE YVES; RUETSCH FLORIAN (2023)
The present disclosure provides compositions and methods for treating peripheral arterial disease in a subject by administering an exonucleotide pyrophosphatase phosphodiesterase-1 (ENPP1) agent or an exonucleotide pyrophosphatase phosphodiesterase-3 (ENPP3) agent. 本公开提供了通过施用外核苷酸焦磷酸酯酶磷酸二酯酶-1(ENPP1)药剂或外核苷酸焦磷酸酯酶磷酸二酯酶-3(ENPP3)治疗受试者的外周动脉疾病的组合物和方法。